Does positional concern matter in poor societies? Evidence from a survey experiment in rural Ethiopia - Alpaslan Akay; Peter Martinsson; Haileselassie Medhin (Institute for the Study of Labor (IZA), 2009)
We investigated attitudes toward positionality among rural farmers in Northern Ethiopia, using a tailored survey experiment. On average, we found positional concerns neither in income per se nor in income from aid projects among the farmers. These results support the claim that positional concerns are positively correlated with absolute level of income of a country.
urn:nbn:de:101:1-20090922111
Keywords: C90; D63; 330; Ethiopia; positional concern; relative income; Sozialer Status; Meinung; Einkommensverteilung; Landwirtschaft; Ländlicher Raum; Äthiopien